Commercial Activities under Commercial Law: Examples from Arab Countries - Abdul-Rahman Sayed Ali; Luqman Raed Ibrahim; Ezzat Shawqi Al-Tamimi (International Journal of Law Research and Studies, 2022)
It is one of the branches of private law and is concerned with regulating commercial businesses. The principle of this law is based on regulating commercial practices between merchants and each other, as well as between merchants and other parties, in line with the applicable legal legislation. Commercial law is concerned with managing commercial conflicts and adjudicating them before the courts, and it also includes Imposing penalties on those who violate legal regulations. Commercial law contains a wide range of laws and rules that regulate contracts, behaviors, and rights of individuals and companies in various commercial sectors. This regulation includes many legal issues such as regulating commercial contracts, taxes, bankruptcy, and financial market transactions. Through these legal frameworks, commercial law seeks to Creating a fair and orderly trade environment that contributes to supporting economic and commercial activities in an effective and sustainable manner. The research reviews the most important definitions of commercial law and its areas of work. It also reviews examples of commercial law applications from some countries in the Arab region. It allows the researcher to learn about the principles on which commercial law is based in each country.